Efeitos da eletroestimulação sobre os parâmetros eletromiográficos e dinamométricos do músculo quadríceps femoral - Farias, Rafaela Soares de (2010)
To analyze the effects of electrical stimulation at two frequencies on the EMG parameters (EMG) and dynamometer, in muscles with different typing. MATERIALS AND METHODS: This is a controlled clinical trial, randomized and double blind. Sixty healthy volunteers (23.6 ± 4.2anos; 54.2 ± 7.7kg, 1.62 ± 0.009 cm) of both sexes were divided randomly into three groups: control group (CG), experimental group 1 (SG1) with application of the current Russian 30 HZ and experimental group 2 (EG2) at 70 Hz The volunteers performed an initial assessment (AV1) on the isokinetic dynamometer with three repetitions maximum voluntary isometric (MVC) for knee extension concomitant uptake of EMG for the VM muscle, VL and RF. Later, after application of NMES, they underwent an experimental protocol of isometric fatigue using 70% of MVIC, ending with the completion of a final assessment (AV2) in the same manner as the AV1. RESULTS: By analyzing the profile of the 60 subjects in three broad, VM showed a higher value of RMS behavior when the VL and RF (p = 0.03 and p = 0.02). With respect to Fmed the RF muscle (p = 0.001) showed a higher value for the VM. The VM muscle showed significant increases of Fmed (p = 0.05) after electrical stimulation at 70 Hz when compared the AV1 AV2 and RF showed significant decreases (p = 0.009) after stimulation at 30 Hz during the fatigue showed an increase RMS in the VM and VL, with a reduction in RF. For the variable Fmed was observed in three broad decline during fatigue. CONCLUSION: Our findings provide evidence that the muscles VM, VL and RF fiber typing are different besides indicating that the frequency of NMES tend to relate to the muscle stimulated. Finally suggests the surface EMG as a noninvasive method for characterizing muscle